Fenomena Judi Online dan Degradasi Moral - Amelia, Yunanda; Ramadhan, Gilang; Sulistiani, Inayah; Ayu Anggraini, Renita; Vindi Astrianan Nur Qalifah, Eka; Muhammad Noor, Aditia (Universitas Nahdlatul Ulama Sunan Giri, 2024)
The phenomenon of gambling is currently not a foreign thing in society. Many people justify all means to get money or wealth instantly without any effort. With the rise of gambling, it can become a community disease that damages the social system of society. The purpose of this research is to find out the various factors that cause people to do online gambling; find out the effects or impacts caused by online gambling; describe the moral degradation that occurs as a result of the phenomenon of online gambling in Indonesia. This research was conducted in Indonesia, namely by understanding the background and collecting data or information related to the research. The research method we took to compile the article is by using a qualitative and descriptive approach. In addition, we also use secondary legal materials, namely from the results of previous studies, scientific articles, and others. The phenomenon of online gambling is influenced by economic factors, environmental factors and entertainment factors. In addition, online gambling also has the impact of complex problems including addiction, mental disorders, economic decline, increased crime and data theft. The existence of online gambling which has become a phenomenon causes people to have a moral crisis, they take various actions just to win gambling. Moral degradation and social values have also decreased due to the deviant use of technology such as in the case of online gambling, such as material values, vital values, and spiritual values.